PENGARUH UKURAN PERUSAHAAN, KONSERVATISME AKUNTANSI, DAN KARAKTER EKSEKUTIF TERHADAP MANAJEMEN PAJAK - Tanjung, Feby Anggraeni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
This study aims to test empirically the effect of the independent variable on thevariabel dependent variable. In this study, the independent variable is firm size,accounting conservatism, and executive character, while the dependentvariable is tax management as measured by the Effective Tax Rate (ETR). Thepopulation of this study uses mining companies listed on the Indonesia StockExchange (BEI) in 2016-2019. The method used was purposive sampling withcertain criteria, which resulted in a sample of 45 data samples. The type of dataused is secondary data. The data analysis used descriptive statistic, classicassumption test, multiple regression analysis, and hypothesis testing usingSPSS 25 software. The results of this study indicate that firm size andaccounting conservatism have no effect on tax management, while executivecharacter has an effect on tax management.